Динамічні характеристики роботи механізму повороту крану на колоні - Коваленко, Валентин Олександрович; Стрижак, Всеволод Вікторович; Іглін, С. П.; Коваленко, Олег Олександрович; Стрижак, Мар'яна Георгіївна (Одеський національний політехнічний університет, 2021)
Стаття присвячена дослідженню коливань і динамічних процесів у механізмах повороту з урахуванням усіх складових динамічного навантаження – високочастотних складових, розгойдування вантажу, дисипації. Наведена кінематична схема механізму повороту крана на колоні. Розглянуто двомасову динамічну модель привід - поворотна частина крану і отримано їїаналітичний розв’язок.

The literature review showed that in the existing mathematical models, the main attention is paid to dynamic processes associated with low-frequency oscillations of the load. The issues of highfrequency vibrations and dynamic processes in metal structures require additional lighting, taking into account all the components of the dynamic load. This approach will make it possible to more accurately determine the magnitude of the forces arising in the bearing elements, thereby increasing the reliability and safety of the operation of hoisting machines. The kinematic diagram of the crane swing mechanism on the column is presented. A two-mass dynamic model of the drive system - the slewing part of the crane is considered. A mathematical model has been compiled, in which standard assumptions are accepted: the swinging of the load is not taken into account, there is an elastic connection between the engine and the driven shaft of the swing mechanism, with all other crane masses reduced to it. Separately presented are graphs calculated from the obtained dependencies: change in dynamic loads during acceleration of the mechanism with constant torque, change in dynamic loads during acceleration of the mechanism, taking into account dissipation, change in dynamic loads in the elements of the mechanism, taking into account the deviation of the cargo ropes, changes in dynamic loads in the elements of the mechanism, taking into account deflections of cargo ropes and dissipation.
Dynamic characteristics of the crane rotation mechanism on the column
Keywords: кран; механізм повороту; динаміка; crane; rotation mechanism; dynamics